MEMBANGUN KURIKULUM DEEP LEARNING UNTUK MEMPERSIAPKAN GENERASI DIGITAL - Waruwu, David El Roy; Tarto (Jurnal Sosialita, 2025)
Technological developments in the era of Industrial Revolution 4.0 and Society 5.0 demand an adaptive education system to prepare a generation capable of competing at the global level. This article discusses the development of a deep learning-based curriculum as an innovative approach to improve students' holistic competencies, covering cognitive, affective, and psychomotor aspects. Using a qualitative method based on a literature review, this research identifies the benefits of a deep learning curriculum, including the strengthening of critical thinking, analytical skills, creativity, and digital literacy. In addition, it supports the personalization of learning through the integration of technologies such as augmented reality, virtual reality, and artificial intelligence. The results show that the deep learning curriculum is able to prepare generation Z and Alpha to face global challenges. However, its implementation faces obstacles such as limited infrastructure, educator readiness, and data privacy issues. The study highlights the importance of collaboration between educational institutions, government and industry, as well as investment in teacher training and provision of supporting technology. In conclusion, deep learning-based curriculum not only offers an innovative solution to improve the quality of education but also a strategic step to build an adaptive and competitive society of learners. This research recommends strengthening education policies and providing digital infrastructure to support the successful implementation of this curriculum. Keywords: Deep learning, Digital Generation, Education Curriculum, Learning Technology, Curriculum Strategy.